Nedostatečná reakce na intravitreální léčbu ranibizumabem u foveomakulární vitellioformní dystrofie s nástupem v dospělosti doprovázené choroidální neovaskularizací. Kazuistika - Berhuni, Mustafa; Tıskaoğlu, Setge Nesime; Ozturkmen, Cem (Česká a slovenská oftalmologie, 2025)
Adult-onset foveomacular vitelliform dystrophy (AOFVD) is a rare disease characterized by accumulation of yellowish deposits in the macula. Rarely, it may be complicated by choroidal neovascularization (CNV). Cases with CNV may be confused with occult CNV in age-related macular degeneration. In our case, we will present the visual and anatomical results of a patient with AOVF-related CNV, in which we administered 3 doses of intravitreal ranibizumab (IVR). A 59-year-old female patient, who attended our clinic with the complaint of decreased vision in both eyes, was diagnosed with AOVF-related CNV in both eyes and was treated with 3 doses of IVR for 3 months. Despite the improvement in visual and anatomical functions 1 month after the first dose, vision decreased, and anatomical functions regressed to the pre-injection state in continued injections. IVR therapy is not an appropriate treatment option in the treatment of AOVF-associated CNV.
Keywords: neovaskularizace choroidey; Bestova nemoc; injekce intravitreální; Ranibizumab; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Angiogenesis Inhibitors; ranibizumab; lidé; Female; Choroidal Neovascularization; ženské pohlaví; lidé středního věku; Humans; inhibitory angiogeneze; Vitelliform Macular Dystrophy; Middle Aged; Intravitreal Injections